Deviant Behavior of Teenagers in Using Social Media at Ternate City - Bailussy, Wahyuni; Kahar, Suyatno (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Communication and information problems that occur in today's digital era, have a major influence on its users; There's no denying that technology can make someone unknown famous, and vice versa. Especially for teenagers, social media has a significant impact. According to research by Septian Wulan, in Indonesia, adolescents aged 15-19 years are the largest internet users, reaching 64%. Fenomene The deviant behavior that grabs the attention of the people of Ternate is the behavior of inhaling glue inside the Oranje fortress which is a historical location for this kieraha earth. This glue inhalation behavior for teenagers was reported by several online media, one of which was SuaraTernate.com with the headline "11 Teenagers in Ternate caught "Ngelem" inside the Oranje fort" on October 6, 2021. Based on the phenomenon that occurs in adolescents in the city of Ternate, researchers conducted research on the behavior of adolescents in the city of Ternate in using social media to find out the behavior of. According to Ahmadi (2009:49), social interaction is a relationship between two or more individuals in which the behavior of one individual influences, changes, or corrects the behavior of another individual, or vice versa. Walgito (2003: 65) explains that social interaction is a relationship among individuals in which one individual can influence another so that mutual influence occurs. The results of the study obtained that teenagers in the city of Ternate have positive and negative behaviors, but the most dominant is positive behavior as well as empathy behavior in interpersonal communication through social media. The average person still has a sense of empathy between friends and others who are still very good, rather than being an individualist teenager, rarely caring about others because of the influence of social media. Because teenagers in the city of Ternate use social media on average as a learning medium.